Recenzió: Emerging African Geopolitics: In the Shadow of Conflicts - Aragaw, Belay Asmare (Afrika Tanulmányok / Hungarian Journal of African Studies, 2025)
Belay Asmare Aragaw a következő művet mutatta be: Huriye Yildrim Cinar, Ferdi Güçyetmez: Emerging African Geopolitics: In The Shadow Of Conflicts. Cambridge Scholars Publishing, 2025. 299 pp.